Foundation in food and nutrition security (CFNI KingstonJM, 1988)
Describes the background to the formation of the CFNI and outlines its functions. Documents the significant activities of the Institute over a period of two decades. These activities include information dissemination through various publications; sponsoring nutrition training courses, workshops, and hosting conferences; carrying out nutrition and consumption surveys in different territories and developing a regional food and nutrition strategy for the region.
IDS